2011
DOI: 10.1177/1534484311417561
|View full text |Cite
|
Sign up to set email alerts
|

Task Types and Team-Level Attributes

Abstract: Within team research, there is no shortage of literature classifying teams. However, the team taxonomic literature suffers from a few limitations. First, many taxonomies claim to classify teams into mutually exclusive classes, yet when examined closely, are not. Second, some of the most well-known taxonomies are descriptive of various tasks teams engage in, but not of the holistic team-level properties that define different types of teams. A clear understanding of both is necessary if human resource developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Team virtuality is concerned with "the degree to which team members do not work in either the same place and/or at the same time" (De Jong, Dirks, & Gillespie, 2016, p. 1136. Collocated teams collaborate face to face, whereas noncollocated teams rely on technologymediated communication (Wildman et al, 2012). With the rapid advancement in information and communication technology, multinational corporations increasingly use noncollocated virtual teams (Connaughton & Shuffler, 2007;Hinds, Liu, & Lyon, 2011;Leung & Peterson, 2011).…”
Section: Team Virtualitymentioning
confidence: 99%
“…Team virtuality is concerned with "the degree to which team members do not work in either the same place and/or at the same time" (De Jong, Dirks, & Gillespie, 2016, p. 1136. Collocated teams collaborate face to face, whereas noncollocated teams rely on technologymediated communication (Wildman et al, 2012). With the rapid advancement in information and communication technology, multinational corporations increasingly use noncollocated virtual teams (Connaughton & Shuffler, 2007;Hinds, Liu, & Lyon, 2011;Leung & Peterson, 2011).…”
Section: Team Virtualitymentioning
confidence: 99%
“…For example, Wildman et al (2012) reported 17 published attempts to create group typologies, and Hollenbeck, Beersma, and Schouten (2012) identified 50 distinct group types across these frameworks. Thus, researchers have identified a need to integrate existing categories into a more inclusive typology based on key structural and task-based team traits (e.g., Devine, 2002;Hollenbeck et al, 2012;Wildman et al, 2012). For example, Wildman et al (2012) integrated the available literature to produce an overall taxonomy of 12 group types and proposed a list of higher-order characteristics that are intended to help researchers describe team types.…”
Section: Group Typologiesmentioning
confidence: 96%
“…The need to assess effectiveness is particularly relevant in this case because the distinctiveness of the group types in the current typology have not been confirmed empirically; a limitation held in common with most other group typologies (e.g., Devine, 2002;Hollenbeck et al, 2012;McGrath, 1984;Steiner, 1972;Wildman et al, 2012). With regard to identifying an ideal classification, the evaluation of typology effectiveness involves three primary aspects: internal validity, external validity, and utility (Fleishman & Zaccaro, 1992).…”
Section: Typology Effectivenessmentioning
confidence: 97%
See 1 more Smart Citation
“…In examining the moderating role of team characteristics, we focus on task interdependence, team virtuality, temporal stability, authority differentiation, and skill differentiation; five structural design features that describe how the team as a whole is composed and organized (Stewart, 2006). Our choice of variables is grounded in two recently developed taxonomic frameworks for classifying and differentiating teams: one developed by Hollenbeck, Beersma, and Schouten (2012), which identifies temporal stability, authority differentiation, and skill differentiation as key features of a team's structural design, and one developed in parallel by Wildman, Thayer, Rosen, Salas, Mathieu, and Rayne (2012), which identifies three similar features 1 , as well as virtuality and task interdependence as two additional features. Including these latter two characteristics adds to the comprehensiveness of our examination, and allows us to address mixed findings regarding their moderator role that have been found across studies on intrateam trust (see Alge et al, 2003;Bierly et al, 2009;Muethel et al, 2012;Staples & Webster, 2008).…”
Section: Moderators Of the Trust-performance Relationshipmentioning
confidence: 99%